Green Supply Chain Management and Environmental Impacts on Public Perception of Electric Vehicle in Indonesia: Model with PLS-SEM and COST APPROACH - Gunawan, Andri; Suryadinata Gorda, A.A.N. Oka; Supriyadinatha Gorda, A.A.N. Eddy; Sri Rahayu Gorda, A.A.A.N.; Latupeirissa, Jonathan Jacob Paul (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this study is to examine green supply chain management on electric vehicles in Indonesia. Variables in this research consisted of green supply chain, non-financial incentives by government and environmental im-pact on public perceptions of electric vehicles. The green supply chain man-agement variables in this study were the value added green supply chain man-agement and registration green supply chain management. The non-financial incentives variables in this research included the provision of public charging station and parking fee exemption. Samples from the study derived from 187 potential buyers of electric vehicles domiciled in Denpasar and Badung, Bali Province. This study adopted Structural Equation Model with SmartPLS as the analysis technique. A cost approach was also applied in this study. The appli-cation of these two methods was to provide a comprehensive understanding of policies related to electric vehicles. In line with other studies, the results of this study demonstrated that all variables had a positive effect on the public perception of electric vehicles. However, the environmental impact variable had the greatest influence at the lowest cost compared to other variables. Non-financial incentives variable exhibited a positive influence at an affordable cost than green supply chain management variable. The green supply chain management variable was confirmed to have a positive effect with the most expensive cost compared to others.